Beautiful or intelligent? Discourse stereotypes and social meanings of phonetic variation among adolescent girls in Vilnius - Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2014)
Combining metalinguistic discourse analysis with statistical and qualitative speaker evaluation analysis the paper examines perceptions of phonetic variation in the speech of urban girls and discusses the impact of social stereotypes on the evaluation of their speech styles. The approach is adapted that speech variants are meaningful elements of a style cluster used by speakers for construction of certain personality types and stances and recognized by hearers as such (Agha 2007, Campbell-Kibler 2009, Blommaert 2010). Subconscious Speaker evaluation experiment was carried out in four upper-secondary schools of Vilnius. 14 female speech samples, representing three supposed speech styles indexed by either open back rounded [ɒ] (variant of standard Lithuanian /o/), or alveolar [s] (variant of dental /s/) or unmarked with regard to the mentioned features were presented for subconscious assessment to 232 students. The students were asked to rate the voices on several 7-point scales to assess the personality traits of the voices and their suitability for several professions. The idea was to investigate whether the students will recognize these speech styles of urban girls as different ways with language, whether this recognition will result in categorisation of speakers into separate social types and whether the discourse stereotypes will impact the assessments of students. The research confirmed the presuppositions. The voices that included an open rounded [ɒ] were subconsciously associated with the social stereotypes that were found in the discursive construction of the pop girls, the so called fyfas. These voices were assessed significantly more negatively on qualities related with personal maturity and trustworthiness, such as not being goal-directed, conscientious and intelligent, and most positively on the trait joyful. As well they were significantly more often associated with fashion, music and advertising branches. The highest intellectual capacities and skills as well prestigious professions such as businessman or physician were attributed to the unmarked voices, relating this speech style to the stereotype of a nerd. Whereas the voices that included alveolar [s] were perceived as belonging to an in between position – on most of the scales their ratings were lower than the unmarked voices’ and higher than the [ɒ] voices’. Such attribution confirmed the hypothesized assignment of alveolar [s] to “serious entertainment”, a style that is presented as serious in entertainment contexts. The research revealed significant association of this style with the music branch. To summarize, the studied speech styles are subject of conscious and subconscious awareness in the Lithuanian speech community. They are reacted to applying certain ideological schemes, be it stereotypes constructed and maintained by the public discourse or subconscious knowledge, formed by social and linguistic competence of the judges. There is no doubt that at least two of the studied styles – the unmarked Vilnius speech and the alveolar [s] including style are not limited to female speakers. The gender variable would be an interesting supplement to the further study of language variation in the Lithuanian capital Vilnius.